2023
DOI: 10.1021/acs.jpcc.3c01041
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Branched Composite Binder via Covalent Grafting for High-Performance Silicon-Based Anodes

Abstract: A binder plays an essential role in preserving the mechanical stability of electrodes and in enhancing the cycle life of Si anodes. Nevertheless, the typical binders normally are not effective enough to relieve the unavoidable volume expansion of Si during cycling. Herein, to make full use of the polar functional groups on the polymer backbone, the citric acid-grafted poly(acrylic acid) (CA-g-PAA) composite binder is rationally designed and prepared by a simple graft modification. The CA molecule not only prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…To address these challenges, the strategic engineering of binders has arisen as a promising solution to enhance the structural integrity and performance of Si-based anodes. According to the movement toward adopting environmentally sustainable materials in the secondary batteries and electric vehicle industries, water-soluble polymeric binders (e.g., carboxymethyl cellulose (CMC), poly­(acrylic acid) (PAA), poly­(vinyl alcohol) (PVA), and so on) have been widely explored. Their abundant polar functional groups, such as −COOH and −OH, in molecules foster hydrogen bonding with hydroxyl groups on the Si surface, effectively mitigating volumetric changes during the battery cycles. , In addition to the linear polymers mentioned above, a rich variety of PAA-based binders were developed through grafting, polymerization, and postmodification because of the easy modification of carboxyl groups in PAA molecules than others. Nonetheless, the slipping of the linear or branched polymer chains during the volume expansion still occurs due to the lack of interchain connections, which challenges the long-term stability of Si electrodes …”
Section: Introductionmentioning
confidence: 99%
“…To address these challenges, the strategic engineering of binders has arisen as a promising solution to enhance the structural integrity and performance of Si-based anodes. According to the movement toward adopting environmentally sustainable materials in the secondary batteries and electric vehicle industries, water-soluble polymeric binders (e.g., carboxymethyl cellulose (CMC), poly­(acrylic acid) (PAA), poly­(vinyl alcohol) (PVA), and so on) have been widely explored. Their abundant polar functional groups, such as −COOH and −OH, in molecules foster hydrogen bonding with hydroxyl groups on the Si surface, effectively mitigating volumetric changes during the battery cycles. , In addition to the linear polymers mentioned above, a rich variety of PAA-based binders were developed through grafting, polymerization, and postmodification because of the easy modification of carboxyl groups in PAA molecules than others. Nonetheless, the slipping of the linear or branched polymer chains during the volume expansion still occurs due to the lack of interchain connections, which challenges the long-term stability of Si electrodes …”
Section: Introductionmentioning
confidence: 99%
“…However, the structural damage and electrode delamination of the Nano-Si anode during cycles remain inevitable challenges. Binder, serving as an adhesive to bind the electrode components, plays a crucial role in retaining the morphology of electrodes and ensuring mechanical stability during battery operations. Recent studies have demonstrated that the elastic binders derived from insulating mechanically interlocked polymers have the ability to alleviate mechanical stress of Si anode generated by dramatic volume change. However, few studies focused on Si anode using elastic binders that can meet the commercial demand of over 3 mAh cm –2 . This arises from the slow ion transfer speed within the thick Si anode, leading to additional interfacial energy barriers and unfavorable concentration gradients (Figure a).…”
mentioning
confidence: 99%